Development Vegetables Organic in Agriculture Urban - Martuti, Nana Kariada Tri; Hadiyanti, Lutfia Nur; Haris, Amnan; Affandi, Erry Kariada Tri; Simbolon, Andri Kariada Tri; Arifin, Mochamad Samsul (Jurnal Abdimas, 2023)
Agriculture agriculture urban with method agriculture organic is A form solution just done _ For face many intervention ingredients synthetic in the world of agriculture. Cultivation vegetables organic on land yard is a worthy alternative considered Because can sufficient need healthy and hygienic food  for family, save expenditure consumption food at a time guard sustainability environment. As for goals from activity devotion to public This namely, to : increase KT Tambakrejo knowledge in cultivation friendly organic vegetables environment, and improve KT Tambakrejo knowledge in making organic fertilizers and pesticides with good and right. Activity devotion to community carried out by KT Tambakrejo, Village Tambakrejo Semarang, at l a kuk a n with a number of method approach which is conducted based group, comprehensive and based local potential. Enhancement knowledge partner done through observation field work, interviews, training, mentoring and evaluation activity. From activities dedication that has been done, obtained results increase knowledge partner in technology raised bed as method repairer suitable soil implemented in the region urban with condition land in general arid, increasing knowledge partner in cultivation vegetables organically and friendly environment. Service partners have also get good and correct knowledge in making organic fertilizers and pesticides, with utilise potency source power existing in the environment surroundings.